Study of the Compatibility of Polymer-Polymer Mixtures in Solution by Dilute-Solution Viscometry Method - Melad, Omar (Asian Journal of Chemistry, 2010)
The viscosity behavior of mixtures of poly(methyl methacrylate) (PMMA) with other polymers such as ploy(vinyl chloride) (PVC), polystyrene (PS) and poly(isobutyl methacrylate) (PiBMA) in dilute tetrahydrofurane (THF) was studied at 29ºC. The ternary systems assayed, and denoted solvent (1)/polymer (2) / polymer (3), poly( methyl methacrylate) PMMA as polymer 2, and poly(vinyl chloride) PVC. poly(styrene) PS and poly(isobutyl methacrylate) PiBMA as polymer 3. The intrinsic viscosity and viscosity interaction parameter were experimentally measured for the binary (solvent/ polymer) as well as for the ternary systems and have served for the estimation of the compatibility of the different mixtures by means of the signs of Δbm and Δ[η]m.